Moving Out of Poverty : Volume 1. Cross-Disciplinary Perspectives on Mobility - Narayan, Deepa; Petesch, Patti (Washington, DC: World Bank and Palgrave Macmillan, 2012)
This volume brings together multidisciplinary perspectives on poor people's mobility, a dynamic approach that hopefully will add to the reader's understanding of how and why people move into and out of poverty. The chapters draw on the latest longitudinal micro data to present a moving picture of poverty that is rather different from what one can see in single snapshots, the staple of traditional poverty analysis. The book is also important because the contributors' distinct disciplinary perspectives demonstrate clearly why it is critical to draw on diverse information to improve the reader's understanding about how to reduce poverty. The economic findings reinforce what has been known for some time: fast economic growth underpins poverty reduction, but the speed of declines in poverty is greatly affected by social and political factors. The economic panels also show that the people mired in chronic poverty around the world are actually fewer in number than the people moving in and out of poverty. Static studies do not capture this dynamic quality of poverty and vulnerability. Of particular interest are the chapters clarifying interactions between the local social, political, and economic factors that underlie persistent poverty, vulnerability, and inequality. They point to the need to draw from different disciplines as we turn to the task of reaching the bottom poor trapped in poverty and those churning in and out of poverty.